Komunikasi Word Of Mouth Dan Pengaruhnya Terhadap Keputusan Dan Kepuasan Mahasiswa Kuliah Di Universitas Dharma Andalas (Unidha) Padang - Haryeni Haryeni; Aulia Mawaddah (LPPM Universitas Dharma Andalas, 2022)
This study aims to determine: (1) The Effect of Word Of Mouth Communication on Student Satisfaction, (2) The Effect of Word Of Mouth Communication on Student Decisions at Unidha, (3) The Effect of Student Decisions on Student Satisfaction at Unidha, (4) The Effect Word of Mouth Communication on Student Decisions Through Student Satisfaction studying at Unidha. The population in this study were students of the S1 Management Study Program, Faculty of Economics and Business, Dharma Andalas University Class of 2019 and 2020, with a total sample of 100 people. The sampling technique used the Accidental Random Sampling method. The data analysis method used partial least squares (PLS). The test results show that Wom Communication has a significant effect on Student Satisfaction, Wom Communication has a significant effect on Student Decisions, Decisions have a positive and significant effect on Student Satisfaction, and Wom Communication has a positive and significant effect on Student Decisions Through Student Satisfaction.